Novel gene targets for miRNA146a and miRNA155 in anterior uveitis. Issue 2 (8th October 2018) - O'Rourke, Micheal; Trenkmann, Michelle; Connolly, Mary; Fearon, Ursula; Murphy, Conor C
Abstract : Background/Aims: Anterior uveitis (AU) is the most common form of intraocular inflammation. MicroRNAs (miRNA) are small, non-coding RNAs functioning as post-transcriptional repressors of gene expression. Knowledge of miRNAs can implicate specific genes and pathogenic signalling pathways in disease. This study examines miRNA expression, function and target genes in AU pathogenesis. Methods: AU and healthy control (HC) peripheral blood mononuclear cells (PBMC) were initially screened for expression of five miRNAs by real-time PCR. Regulation of the aberrantly expressed miRNAs by TLR1/2, TLR3, TLR4, IL1β and TNFα was quantified by real-time PCR and paired cytokine outputs measured by ELISA. Functional effects of miRNA overexpression using transfected THP1 cells examined IL6, IL8, IL10 and IL1β cytokine outputs by ELISA. Target genes were identified using TargetScan online computational algorithm and relevant targets verified by cloning of the 3′UTR and luciferase reporter gene assays. Results: Increased expression of miRNA146a (p<0.01), miRNA155 (p<0.05) and miRNA125a5p (p<0.01) was demonstrated in AU PBMC compared with HC. miRNA155 was increased following TLR1/2 (p<0.05) and TLR4 (p<0.05) stimulation and miRNA146a increased in response to IL1β (p<0.05). In a proinflammatory environment, miRNA155 overexpression in THP1 cells yielded increased cytokine output whereas miRNA146a overexpression showed decreased cytokine output. CD80, PRKCE and VASN were confirmed as novel targets for miRNA146a and SMAD2, TYRP1 and FBXO22 for miRNA155. Conclusion: This study identifies overexpression of proinflammatory miRNA155, regulatory miRNA146a and miRNA125a-5p in AU. CD80, PRKCE and VASN are novel miRNA146a targets and SMAD2, TYRP1 and FBXO22 are novel targets for miRNA155.